2002
DOI: 10.1086/338507
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Circinus X‐1 Broadband Spectrum at Orbital Phases Close to the Apoastron

Abstract: We report on the results of a BeppoSAX (1.8È200 keV) observation of the peculiar X-ray binary source Circinus X-1 (Cir X-1) at the orbital phases between 0.61 and 0.63. We Ðnd that three components are needed to Ðt the broadband spectrum : a blackbody component at a temperature of D0.6 keV ; a Comptonized component with a seed-photon temperature of D1.2 keV, electron temperature of D6 keV, and optical depth of D1.7 ; and a power-law component dominating the spectrum at energies higher than 20 keV. We interpret… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 25 publications
5
42
0
Order By: Relevance
“…The data at phases 0.62-0.84 are The data correspond to the phase interval 0.62-0.84 assuming the ephemeris as reported by Stewart et al (1991). The bin time is 550 s. (Iaria et al 2001a), the data at phases 0.61-0.63 (Iaria et al 2002), and the data at phases 0.62-0.84 (this paper). The bin time is 137 s. at the top right in this figure, while the data of the previous BeppoSAX observation at phases 0.61-0.63 show lower values of both the hard and the soft color.…”
Section: Observationsmentioning
confidence: 97%
See 1 more Smart Citation
“…The data at phases 0.62-0.84 are The data correspond to the phase interval 0.62-0.84 assuming the ephemeris as reported by Stewart et al (1991). The bin time is 550 s. (Iaria et al 2001a), the data at phases 0.61-0.63 (Iaria et al 2002), and the data at phases 0.62-0.84 (this paper). The bin time is 137 s. at the top right in this figure, while the data of the previous BeppoSAX observation at phases 0.61-0.63 show lower values of both the hard and the soft color.…”
Section: Observationsmentioning
confidence: 97%
“…To fit the seven spectra corresponding to the observation taken at phases 0.62-0.84, we used the Comptonization model Comptt (Titarchuk 1994), to which we added a blackbody component at low energies in agreement with Iaria et al (2002), who studied the source at similar phases. This model gave a 2 /dof of 285/202, 364/200, 330/200, 254/201, 244/199, 249/199, and 256/200, respectively, for spectra 1-7; in Table 3 we show the corresponding best-fit parameters.…”
Section: The Soft Excess Below 1 Kevmentioning
confidence: 99%
“…serx1_ref_mod_2 Iaria et al 2001Iaria et al , 2002, and this component may also be present in the spectrum of Ser X-1 (see Miller et al 2013). Unless it is specified otherwise, for every fit, we froze the power-law photon index to the value found by Miller et al (2013) for Ser X-1, that is 3.2.…”
Section: Nustar Spectral Analysismentioning
confidence: 99%
“…A hard X-ray tail of GX 340+0 was also detected in its BeppoSAX spectra (Lavagetto et al 2004). Using the BeppoSAX observations for Cir X-1, which hosts an elliptical orbit with high eccentricity (e ∼ 0.7-0.9), Iaria et al (2001Iaria et al ( , 2002) studied its broadband spectra near the periastron (orbital phase 0) or at the orbital phases close to the apoastron (orbital phase 0.5) and detected similar hard X-ray tails with photon index ∼3.2 during the two orbital episodes. Interestingly, analyzing RXTE data, Ding et al (2006b) found orbital modulation for the hard X-ray emission of Cir X-1.…”
Section: Introductionmentioning
confidence: 99%